Twelve years with a capitation payment system in Swedish dental care: longitudinal development of oral health - Charlotte Andrén Andås; Magnus Hakeberg (BMC, 2021)
Abstract Background Since 2007, patients receiving oral health care within the Public Dental Service in Sweden have had the possibility to choose between the traditional fee-for-service (FFS) payment system or the new capitation payment system, 'Dental Care for Health' (DCH). Payment models are believed to involve different incentive structures for patients and caregivers. In theory, different incentives may lead to differences in health-related outcomes, and the research has been inconclusive. This 12-year longitudinal prospective cohort study of patients in regular dental care analyzes oral health development and self-reported oral health in relation to the patients' level of education in the two payment systems, and compares with the results from an earlier 6-year follow-up. Methods Information was obtained through a questionnaire and from a register from n = 5877 individuals who kept their original choice of payment model for 12 years, 1650 patients in DCH and 4227 in FFS, in the Public Dental Service in Region Västra Götaland, Sweden. The data comprised manifest caries prevalence, levels of self-reported oral health and education, and choice of dental care payment model. Analyses were performed with chi square and multivariable regression analysis. Results The findings from the 6-year follow-up were essentially maintained at the 12-year examination, showing that the pre-baseline caries prevalence is the most influential factor for less favorable oral health development in terms of the resulting caries prevalence. Educational level (≥ university) showed an increased influence on the risk of higher caries prevalence after 12 years and differed between payment models with regard to the relation to self-rated oral health. Conclusions Differences in health and health-influencing properties between payment models were sustained from 6 to 12 years. Strategies for making use of potential compensatory mechanisms within the capitation payment system to increase oral health equality should be considered.